(untitled) (Research, Society and Development, 2023)
Introduction: The management of mental disorders has always been a relevant object of study for medicine, and there are various ways of going about it. Based on the Primary Health Care (PHC) approach, these pathologies have had their forms of management altered over time, and it is necessary to analyze these changes. Objective: The aim of this study was to evaluate the historical, epidemiological and organizational aspects of the management of mental health cases in primary health care, building on knowledge based on case reports and established theoretical frameworks. Materials and Methods: This is an integrative literature review on the management of mental health in primary health care. The PICO strategy was used to develop the guiding question. In addition, the descriptors "Mental Health"; "Primary Health Care"; "Humanization" were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The studies showed different ways of managing mental disorders in PHC, emphasizing the historical construction of the current approach model, the importance of humanization in this process, the central role of Primary Care and the difficulties inherent in psychiatric diagnosis. Conclusion: It was shown that there is a positive integration between the principles and precepts of PHC in the management of psychiatric disorders, enabling more humanized and holistic care for these patients at this level of care.